Đạo hàm
Y=(9-4x)√7-2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`a)TXĐ:R\\{1;1/3}`
`y'=[-4(6x-4)]/[(3x^2-4x+1)^5]`
`b)TXĐ:R`
`y'=2x. 3^[x^2-1] ln 3-e^[-x+1]`
`c)TXĐ: (4;+oo)`
`y'=[2x-4]/[x^2-4x]+2/[(2x-1).ln 3]`
`d)TXĐ:(0;+oo)`
`y'=ln x+2/[(x+1)^2].2^[[x-1]/[x+1]].ln 2`
`e)TXĐ:(-oo;-1)uu(1;+oo)`
`y'=-7x^[-8]-[2x]/[x^2-1]`
Lời giải:
a.
$y'=-4(3x^2-4x+1)^{-5}(3x^2-4x+1)'$
$=-4(3x^2-4x+1)^{-5}(6x-4)$
$=-8(3x-2)(3x^2-4x+1)^{-5}$
b.
$y'=(3^{x^2-1})'+(e^{-x+1})'$
$=(x^2-1)'3^{x^2-1}\ln 3 + (-x+1)'e^{-x+1}$
$=2x.3^{x^2-1}.\ln 3 -e^{-x+1}$
c.
$y'=\frac{(x^2-4x)'}{x^2-4x}+\frac{(2x-1)'}{(2x-1)\ln 3}$
$=\frac{2x-4}{x^2-4x}+\frac{2}{(2x-1)\ln 3}$
d.
\(y'=(x\ln x)'+(2^{\frac{x-1}{x+1}})'=x(\ln x)'+x'\ln x+(\frac{x-1}{x+1})'.2^{\frac{x-1}{x+1}}\ln 2\)
\(=x.\frac{1}{x}+\ln x+\frac{2}{(x+1)^2}.2^{\frac{x-1}{x+1}}\ln 2\\ =1+\ln x+\frac{2^{\frac{2x}{x+1}}\ln 2}{(x+1)^2}\)
e.
\(y'=-7x^{-8}-\frac{(x^2-1)'}{x^2-1}=-7x^{-8}-\frac{2x}{x^2-1}\)
y ' = ( 4 x + 1 ) ' . x 2 + 2 − ( 4 x + 1 ) . ( x 2 + 2 ) ' x 2 + 2 = 4. x 2 + 2 − ( 4 x + 1 ) . x x 2 + 2 x 2 + 2 = 4 ( x 2 + 2 ) − ( 4 x + 1 ) . x ( x 2 + 2 ) . x 2 + 2 = − x + 8 ( x 2 + 2 ) . x 2 + 2
ĐÁP ÁN D
\(y'=\dfrac{1}{4}\left(x^2-4x+10\right)^{-\dfrac{3}{4}}\left(x^2-4x+10\right)'\)
\(=\dfrac{x-2}{2\sqrt[4]{\left(x^2-4x+10\right)^3}}\)
tham khảo:
a)y′=2\(^{3x-x^2}\).ln2.(3−2x)
b) y′\(\dfrac{4}{ln3}\).\(\dfrac{1}{4x+1}\).4=\(\dfrac{4}{\left(4x+1\right)ln3}\)
a: \(y'=\left(x^2\right)'+\left(3x\right)'-\left(6x^6\right)'+\left(\dfrac{2x-3}{x-1}\right)'\)
\(=2x+3-6\cdot6x^5+\dfrac{\left(2x-3\right)'\left(x-1\right)-\left(2x-3\right)\left(x-1\right)'}{\left(x-1\right)^2}\)
\(=-36x^5+2x+3+\dfrac{2\left(x-1\right)-2x+3}{\left(x-1\right)^2}\)
\(=-36x^5+2x+3+\dfrac{1}{\left(x-1\right)^2}\)
b: \(\left(\sqrt{2x^2-3x+1}\right)'=\dfrac{\left(2x^2-3x+1\right)'}{2\sqrt{2x^2-3x+1}}\)
\(=\dfrac{4x-3}{2\sqrt{2x^2-3x+1}}\)
\(y'=3\cdot2x-4+\dfrac{4x-3}{2\sqrt{2x^2-3x+1}}\)
\(=6x-4+\dfrac{4x-3}{2\sqrt{2x^2-3x+1}}\)
c: \(\left(\sqrt{4x^2-3x+1}\right)'=\dfrac{\left(4x^2-3x+1\right)'}{2\sqrt{4x^2-3x+1}}\)
\(=\dfrac{8x-3}{2\sqrt{4x^2-3x+1}}\)
\(y'=\left(\sqrt{4x^2-3x+1}\right)'-4'=\dfrac{8x-3}{2\sqrt{4x^2-3x+1}}\)
Đây là lấy vị chia